Review of International Marketing Management (International Journal of Innovative Research in Engineering & Management, 2021)
As the pace of globalization increases, it is becoming more  essential for companies to guarantee that they are able to  effectively adapt to relevant customer needs and preferences in the  countries in which they operate. Excellence in policy development  and implementation is essential for both transnational and  multinational governments in this regard. This requires constant,  customer-focused explanation and confirmation regarding where  and when the associated administrations are going, as well as how  they may get to their intended prospective roles. As the pace of  globalization increases, it is becoming more essential for  companies to guarantee that they are able to effectively adapt to  relevant customer needs and preferences in the countries in which  they operate. Excellence in policy development and  implementation is essential for both transnational and  multinational governments in this regard. This requires constant,  customer-focused explanation and confirmation regarding where  and when the associated administrations are going, as well as how  they may get to their intended prospective roles.
Keywords: Businesses; Consumer; Marketing; International; Pricing